Analisis Peningkatan Potensi Ekonomi Desa Melalui Pemberdayaan Industri Kecil Menengah (IKM) Berbasis Teknologi Pada Masyarakat Nelayan Desa Sirukkungon Kabupaten Toba Sumatera Utara - Eka Pratiwi Septania Parapat; Ricat Berlien (Owner : Riset dan Jurnal Akuntansi, 2022)
The backwardness of Sirukkungon Ajibata Village as one of the tourist villages in Toba Regency is the phenomenon behind this research. Sirukkungon village is a village located around Lake Toba, which is why the fish farm in Sirukkungon utilizes cages in Lake Toba. The majority of the residents of Sirukkungon Village are fishermen, fishermen with low economic levels. From the results of the initial survey, researchers found facts in the field that Sirukkungon Village is very rich in lake ecosystems that are still very natural, so there are lots of freshwater fish there. In addition, the natural conditions are very beautiful and beautiful to be the main attraction. However, as a tourist village, Sirukkungon is still very far behind compared to other villages. The condition of community resources that are classified as low, the mindset that is still closed and there is no role for technology makes this village left behind. It is hoped that the results of this study can answer the economic problems of Sirukkungon village through the application of the strategies offered. The research method used is descriptive qualitative using IFAS and EFAS matrices in SWOT analysis where the researcher is the research tool. The results of this study are technology-based IKM Empowerment has a high potential for success because villages have strengths and opportunities that are greater than weaknesses and threats.